Conserved molecular signatures of hygrosensory neurons in two dipteran species - Kristina Corthals; Ganesh Giri; Johan Reimegård; Allison Churcher; Anders Enjin (PLoS ONE, 2026)
Small poikilothermic animals like insects rely on environmental sensing for survival. The ability to detect humidity through specialized sensory neurons is particularly critical, allowing them to maintain water balance across diverse environments. While recent studies have identified key receptors associated with humidity sensing, our understanding of the underlying molecular architecture of these sensory systems remains incomplete. Here, we conducted a comparative analysis of single-nucleus transcriptomes of humidity receptor neurons (HRNs) between the vinegar fly Drosophila melanogaster and the yellow fever mosquito Aedes aegypti . We identified 21 shared genes that contribute to the molecular identity of HRNs in both species. These genes encode proteins involved in transcriptional regulation, cellular signalling, enzymatic pathways and cellular organization. Through behavioural analyses, we demonstrate that two of these genes, the serotonin receptor 5-HT7 and the kinesin motor protein Kif19A , are both necessary for humidity-guided behaviours in adult flies. The conservation of these genes between species separated by over 150 million years of evolution suggests shared functional requirements for humidity sensing in dipterans. Our findings provide insights into fundamental principles of sensory neuron organization and offer a framework for understanding how specialized sensory systems evolve and maintain their function.